Impact of the COVID‐19 pandemic on medical genetics and genomics training: Perspective from clinical trainees. Issue 7 (26th March 2022) - Chenbhanich, Jirat; Slavotinek, Anne; Tam, Allison
Abstract: We sought to understand how the coronavirus disease 2019 (COVID‐19) pandemic has affected the well‐being, clinical training, and medical education for clinical trainees in medical genetics and genomics residency and fellowship programs. All clinical genetics trainees in the Accreditation Council for Graduate Medical Education (ACGME)‐accredited training programs were invited to complete a survey. 31 out of 174 trainees completed the survey. With regards to well‐being, 18 trainees reported increased anxiety, 10 had increased depression, 3 increased financial strain, 13 worsening work‐life balance, and 13 worsening physical health. There was increased telehealth utilization in both outpatient (3% before the pandemic vs. 67% during the pandemic) and inpatient clinical encounters (0% vs. 29%). The most commonly reported challenges in telehealth use were inadequate physical examination and technical problems during visits. Twenty trainees believed that the pandemic has negatively impacted overall clinical training while none reported a positive impact. We concluded that the COVID‐19 pandemic has negatively impacted most clinical genetics trainees in ACGME‐accredited training programs. Telehealth has been increasingly used with some challenges. Further studies are needed on how to optimally integrate what we have learned into the training of medical genetics and genomics in the post‐pandemic era.